150423 初版 150423 更新
x |
-4 |
-3 |
-2 |
-1 |
0 |
1 |
2 |
3 |
4 |
|x-1| |
5 |
4 |
3 |
2 |
1 |
0 |
1 |
2 |
3 |
3x |
-12 |
-9 |
-6 |
-3 |
0 |
3 |
6 |
9 |
12 |
x |
-4 |
-3 |
-2 |
-1 |
0 |
1 |
2 |
3 |
4 |
|x-1| |
5 |
4 |
3 |
2 |
1 |
0 |
1 |
2 |
3 |
x-1 |
-5 |
-4 |
-3 |
-2 |
-1 |
0 |
1 |
2 |
3 |
-(x-1) |
5 |
4 |
3 |
2 |
1 |
0 |
-1 |
-2 |
-3 |
|x - 1| は x ≧ 1 のとき x - 1, x < 1 のとき -x + 1 である。
方程式 |x - 1| = 3x は
「x ≧ 1 かつ x - 1 = 3x」 または 「x < 1 かつ -x + 1 = 3x」… ①
と同じである。
① ⇔ 「なし」 または 「x = \(\dfrac{1}{4}\)」
よって, x = \(\dfrac{1}{4}\)
不等式 |x - 1| < 3x は
「x ≧ 1 かつ x - 1 < 3x」 または 「x < 1 かつ -x + 1 < 3x」… ②
と同じである。
② ⇔ 「x ≧ 1」 または 「\(\dfrac{1}{4}\) < x < 1」
よって, x > \(\dfrac{1}{4}\)
不等式 |x - 1| > 3x は
「x ≧ 1 かつ x - 1 > 3x」 または 「x < 1 かつ -x + 1 > 3x」… ③
と同じである。
③ ⇔ 「なし」 または 「x < \(\dfrac{1}{4}\)」
よって, x < \(\dfrac{1}{4}\)
参考 こちら
問題 こちら